2019
DOI: 10.1002/ejoc.201900268
|View full text |Cite
|
Sign up to set email alerts
|

Pioneering Work on Catenanes, Rotaxanes, and a Knotane in the University of Freiburg 1958–1988

Abstract: Research at the University of Freiburg is summarized which aimed at realizing catenanes, rotaxanes, and a molecular knot from 61–62 until 41 years ago. Taking a fresh view at ansa‐compounds – distinct from those in which he had been interested for other reasons before – Arthur Lüttringhaus began to tackle syntheses of catenanes in 1957. The first isolation of a pure catenane (37) succeeded in 1964 jointly with Gottfried Schill. Most of the progress made in the sequel was due to Schill alone or achieved under h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 114 publications
(386 reference statements)
0
19
0
Order By: Relevance
“…Covalent templates and scaffolds were used in many early attempts at the synthesis of interlocked and entwined molecules. 88 Schill, one of the pioneers of this approach, was unsuccessful in efforts to synthesize a molecular trefoil knot using a covalent template based on quinone. 89 The failure was partly due to the lengthy and rather convoluted synthesis necessary because of the synthetic methods available at the time, but removing the template attached to the putative knotted strand through several chemically robust covalent bonds was also problematic.…”
Section: Synthesis Of Molecular Knotsmentioning
confidence: 99%
“…Covalent templates and scaffolds were used in many early attempts at the synthesis of interlocked and entwined molecules. 88 Schill, one of the pioneers of this approach, was unsuccessful in efforts to synthesize a molecular trefoil knot using a covalent template based on quinone. 89 The failure was partly due to the lengthy and rather convoluted synthesis necessary because of the synthetic methods available at the time, but removing the template attached to the putative knotted strand through several chemically robust covalent bonds was also problematic.…”
Section: Synthesis Of Molecular Knotsmentioning
confidence: 99%
“…For this work however, we were specially inspired by Schill and colleagues, who, by the synthesis of a catenane, prepared a MiM for the first time and pioneered the field of covalently templated MiM synthesis [25–27] . In one study (Scheme 1, route A ), they took advantage of a directing ketal group to join a macrocycle (in red) to a properly functionalized linear thread (in blue) in a perpendicular fashion [28] .…”
Section: Methodsmentioning
confidence: 99%
“…[23,24] For this work however,w ew eres pecially inspiredb yS chill and colleagues, who,b yt he synthesis of ac atenane,p repared aM iM for the first time and pioneered the field of covalently templated MiM synthesis. [25][26][27] In one study (Scheme 1, route A), they took advantage of ad irectingk etal group to join am acrocycle (in red) to ap roperly functionalized linear thread( in blue) in ap erpendicular fashion. [28] The resulting intermediate can adopt two conformations, ap rerotaxane-like one 1,w ith the threadp ositioned within the ring, and at rivial one 1',w hich are in an equilibrium lying far to the left.…”
mentioning
confidence: 99%
“…Inspired by the landmark works by Schill, [21] van Maarseveen recently reported an elegant strategy to synthesize [2]catenanes via dynamic covalent templating. The authors had previously reported a way to control conformation of linear molecular chains to access so called quasi [1]catenanes and quasi [1]rotaxanes -molecules with shapes resembling rotaxanes and catenanes but where the different components are permanently connected with covalent bonds.…”
Section: Dynamic Covalent Templatesmentioning
confidence: 99%
“…[14] Using these reversible covalent bonds, unique dynamic applications in for example sensors, [15][16] functional materials [17] and biomaterials, [18] catalysis, [19] as well as drug discovery [20] have been reported. Although the usefulness of conditionally reversible covalent bonds for assembling mechanically interlocked molecules was recognized early on, [21] it is only recently that dynamic covalent chemistry has been used extensively for the synthesis of rotaxanes, catenanes and knots. [22][23] Dynamic exchange in MIMs can be used for either synthetic or functional purposes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%